What does nature sell? Representations of a nature in the media (Research, Society and Development, 2021)
This article analyzes the representations about nature for the “Globo Natureza” campaign. The work analyzes which images and symbolic meanings associated with this theme are disseminated to the Brazilian population. To this end, we analyzed 116 video-minutes produced between the years 2016 and 2019, available on Rede Globo's G1 platform. The focus of the analyzes was: description, images and keywords attributed to the videos, followed by a content analysis. Eight (08) themes were identified. The categorization took into account the content and central words of the headlines of the reports over the years available. The study shows that the representations of nature for the “Globo Natureza” campaign are diverse and marked by the stereotype of an environment characterized by contents that refer to the meanings of the wild, composed of waters, forests and animals, with little or no human interference and with a strong commercial bias, becoming a strategy product for its sponsors.